2020
DOI: 10.1093/nar/gkaa329
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR–Cas12a system in fission yeast for multiplex genomic editing and CRISPR interference

Abstract: The CRISPR–Cas12a is a class II, type V clustered regularly interspaced short palindromic repeat (CRISPR) system with both RNase and DNase activity. Compared to the CRISPR–Cas9 system, it recognizes T-rich PAM sequences and has the advantage of multiplex genomic editing. Here, in fission yeast Schizosaccharomyces pombe, we successfully implemented the CRISPR–Cas12a system for versatile genomic editing and manipulation. In addition to the rrk1 promoter, we used new pol II promoters from endogenous coding genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…The intrinsic RNase activity of Cas12a also allows for an additional design of RNAP II expressed gRNAs, whereby a spacer is flanked by two direct repeats. In this case, the two direct repeats are recognized by Cas12a and the pre-crRNA is processed into its mature form of a spacer and a single direct repeat ( 28 ). Promoters recognized by RNAP II are generally well-characterized, exhibit a wide range of strengths and many are able to dynamically respond to changes in environmental conditions or the presence of an inducer molecule allowing for gRNA expression to be dynamically controlled ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic RNase activity of Cas12a also allows for an additional design of RNAP II expressed gRNAs, whereby a spacer is flanked by two direct repeats. In this case, the two direct repeats are recognized by Cas12a and the pre-crRNA is processed into its mature form of a spacer and a single direct repeat ( 28 ). Promoters recognized by RNAP II are generally well-characterized, exhibit a wide range of strengths and many are able to dynamically respond to changes in environmental conditions or the presence of an inducer molecule allowing for gRNA expression to be dynamically controlled ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Promoters recognized by RNAP II are generally well-characterized, exhibit a wide range of strengths and many are able to dynamically respond to changes in environmental conditions or the presence of an inducer molecule allowing for gRNA expression to be dynamically controlled ( 54 ). A recent study on Cas12a-mediated genome editing showed that driving gRNA expression from a RNAP II promoter increased gRNA availability and improved editing efficiency ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other approach to bypass the limitation of PAM is to employ another CRISPR-Cas system with different PAM specificity. Recently, it was reported that a type V CRISPR system, CRISPR-Cas12a, is applicable for CRISPRi in fission yeast ( Zhao and Boeke 2020 ). Since Cas12a has a T-rich PAM, 5′-TTTV-3′ (V is A, G, or C), Cas12a and Cas9, for which PAM is G-rich and short 5′-NGG-3′, complement each other to cover wide variety of target sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a CRISPRi method based on the CRISPR-Cas12a system was established in S. pombe ( Zhao and Boeke 2020 ). However, to our knowledge, CRISPRi mediated by dCas9 had not been implemented in this organism.…”
Section: Introductionmentioning
confidence: 99%